2022
DOI: 10.1016/s2214-109x(21)00458-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of universal HIV testing and treatment on socioeconomic wellbeing in rural Kenya and Uganda: a cluster-randomised controlled trial

Abstract: Background Universal testing and treatment for HIV has shown promise as an approach to reduce mortality and lower HIV incidence. Evidence on the economic effects of this approach on individuals and households in lowresource settings is scarce. We aimed to examine the effect of universal HIV testing and treatment on a range of economic outcomes. MethodsWe collected data in household surveys done over a 3-year period in a sample of HIV-positive and HIV-negative adults participating in a cluster-randomised trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… 35 63 64 80 81 83 In a randomised controlled trial in Kenya, universal HIV testing and treatment increased primary school completion by 7% among children in households with adults diagnosed with HIV after 3 years of intervention. 81 In another Kenyan study, weekly hours of children’s school attendance increased by over 20% within 6 months after ART initiation by the adult person living with HIV. 80 Similarly, in Malawi, ART availability increased expenditures on education and schooling outcomes, including among individuals not living with HIV who did not directly benefit from ART.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 63 64 80 81 83 In a randomised controlled trial in Kenya, universal HIV testing and treatment increased primary school completion by 7% among children in households with adults diagnosed with HIV after 3 years of intervention. 81 In another Kenyan study, weekly hours of children’s school attendance increased by over 20% within 6 months after ART initiation by the adult person living with HIV. 80 Similarly, in Malawi, ART availability increased expenditures on education and schooling outcomes, including among individuals not living with HIV who did not directly benefit from ART.…”
Section: Resultsmentioning
confidence: 99%
“… 69 We identified one randomised controlled trial which examined the effect of universal HIV testing and treatment on economic outcomes of household members. 81 In figure 2 , we map the number of articles by country in SSA. Most single-country studies were from Uganda, South Africa and Kenya, whereas four studies used multicountry data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From full‐text review, we identified 41 records (manuscripts or abstracts) representing 28 unique studies meeting our inclusion criteria. The SEARCH trial [ 29 ] included four unique study reports (different study populations or outcomes) [ 30 , 31 , 32 , 33 ]. The Community Score Card study had two unique study reports [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…HIV care continuum outcomes. Eight studies included individualized counselling and patient-centred communication as the main intervention [30,31,47,49,54,[57][58][59] and six studies had a comparison group [37,40,56,58,65,66]. Among them, three studies (50%) reported that the intervention had a positive effect on at least one of the HIV care continuum outcomes reported [50,58,65] (Table 2).…”
Section: Individualized Counselling and Patient-centred Communicationmentioning
confidence: 99%